2006
DOI: 10.1124/mol.106.023473
|View full text |Cite
|
Sign up to set email alerts
|

State-Dependent Verapamil Block of the Cloned Human Cav3.1 T-Type Ca2+ Channel

Abstract: Verapamil is a potent phenylalkylamine antihypertensive believed to exert its therapeutic effect primarily by blocking highvoltage-activated L-type calcium channels. It was the first clinically used calcium channel blocker and remains in clinical use, although it has been eclipsed by other calcium channel blockers because of its short half-life and interactions with other channels. In addition to blocking L-type channels, it has been reported to block T-type (low-voltage activated) calcium channels. This type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 38 publications
1
37
0
Order By: Relevance
“…Verapamil produces tonic block (i.e., block at the resting potential), measured with infrequent depolarizations, in both T-type and L-type channels. In heterologous expression systems, the affinity of verapamil is similar, with an ED 50 for L-type channels of ϳ10 M, versus an ED 50 of ϳ20 M for T-type channels (Johnson et al, 1996;Freeze et al, 2006). D888 is a much higher-affinity ligand for L-type channels than verapamil, with an ED 50 for closed channel block of ϳ50 nM (Johnson et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Verapamil produces tonic block (i.e., block at the resting potential), measured with infrequent depolarizations, in both T-type and L-type channels. In heterologous expression systems, the affinity of verapamil is similar, with an ED 50 for L-type channels of ϳ10 M, versus an ED 50 of ϳ20 M for T-type channels (Johnson et al, 1996;Freeze et al, 2006). D888 is a much higher-affinity ligand for L-type channels than verapamil, with an ED 50 for closed channel block of ϳ50 nM (Johnson et al, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, D888 has 5-fold higher affinity for depolarized than for resting L-type channels (Johnson et al, 1996). In T-type channels, block by verapamil is modestly use-dependent (Freeze et al, 2006). We tested the use-dependence of D888 using a train of 25-ms depolarizing pulses to Ϫ10 mV with an interpulse interval of 100 ms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, stably expressed human Ca v 3.1 T-type channels in human embryonic kidney (HEK) cells were blocked by verapamil in a use-and voltagedependent manner with an IC 50 of 21.4 µM and the drug significantly slowed the recovery from inactivation. It was suggested that verapamil achieves its inhibitory effect via occlusion of the channel pore associated with an open/inactivated conformation of the channel [54]. 10 µM diltiazem (which reduced I Ca,L by 18 %) had no action on T-type calcium channels in guinea-pig ventricular myocytes [47] but in rat aorta SMCs it reduced I Ca,T with an IC 50 of 30 µM, ten times less potently than I Ca,L .…”
Section: Actions On the L-type Calcium Channelsmentioning
confidence: 99%
“…4. Prolongation of the recovery from inactivation of calcium channels was described with verapamil [54], bepridil [35], semotiadil and also with diltiazem [39]. This alteration of channel behavior can also contribute to the antiarrhythmic action of CCAs by increasing the refractory period (RP) of nodal tissues.…”
Section: Potential Mechanisms Behind the Antiarrhythmic Actions Of Ccasmentioning
confidence: 99%